High step‐up interleaved boost converter utilising stacked half‐bridge rectifier configuration. Issue 17 (30th April 2019) - Muhammad, Musbahu; Lambert, S.; Armstrong, M.; Pickert, V.
Abstract : This paper proposes a solution to complement the insufficient voltage gain and voltage stress distribution of classical interleaved boost converter in high step‐up application. An interleaved converter integrating coupled inductor and voltage multiplier cell, which provides an additional voltage gain is proposed. By stacking the secondary side of the interleaved coupled inductor to its primary side, a high step‐up voltage gain and distributed voltage stress are realised. Low‐voltage rated devices ultimately reduce the conduction losses. The principle of operation and the performance characteristic of the converter are presented and verified by an experimental prototype of 140 W, 12 V input, and 120 V output.